Foster children are at risk for developing problems in social-emotional functioning: A follow-up study at 8 years of age. (January 2020) - Jacobsen, Heidi; Bergsund, Hans Bugge; Wentzel-Larsen, Tore; Smith, Lars; Moe, Vibeke
Highlights: Foster children are at risk for developing problems in social-emotional functioning. Mean scores of foster children's problem behavior were in the normal range. More foster children had externalizing scores in the borderline/clinical range. Externalizing behavior at age 2 and 3 years predicted such behavior at age 8 years. Abstract: Foster children are at risk for becoming less well-adjusted in their social-emotional functioning due to possible abuse and neglect prior to placement. There is no consistent evidence that foster children's social-emotional functioning improves in foster care, and externalizing behavior has specifically been linked to placement disruption. Investigations of foster children's functioning over time and with multiple informants are scarce. Our first aim was to investigate foster children's social-emotional functioning (externalizing, internalizing and total problem behavior) reported by female and male caregivers, as well as by teachers, at 8 years (T3) of age, as compared with a non-foster group. Our second aim was to investigate the predictive power of internalizing and externalizing behavior from age 2 (T1) and 3 years (T2). Results showed that foster children were reported to show more problem behavior at age 8 years compared to the comparison children, although their scores were within the normal range. Externalizing behavior reported by foster mothers at age 2 and 3 years, and by foster fathers at age 3, strongly predicted externalizing behavior at age 8 years. The results suggest that social-emotional functioning in early childhood predicts externalizing and internalizing behavior in middle childhood. This study highlights the clinical importance of investigating such behavior among young foster children in order to help them move towards a healthy developmental pathway in early school years.